DETERMINATION OF HORIZONTAL LIP POSITION IN RELATION TO REFERENCE LINES - Kovačević, Olivera; Erić, Mirela (Medicinski podmladak, 2024)
Аbstract Introduction: Facial beauty mostly depends on the correct mutual relations of the upper and lower jaw, along with the jaw and teeth, which results in different convexity and shape of the lips, causing the unique morphology of an individual’s lips. Goal: Research aims were to determine the morphometric differences of the horizontal position of the lips in relation to the reference lines and sex of the subjects. Material and Methods: The research was conducted on 60 subjects (30 males/30 females), students of Medical Faculty in Novi Sad, ages 18 to 20. Facial profile photos of each subject were taken in the Frankfurt plain position. After marking the reference lines in the Paint program, measurements were performed using the program ImageJ 1.48v. Results: The average distance of the upper and lower lip from the Ricketts line in males was 7.48/5.42 mm, in females 5.82/3.87 mm; from the Steiner line in men was 2.80/2.49 mm, in females 1.99/2.21 mm; from the Burstone line in males was 2.48/2.14 mm, in females 2.88/2.38 mm; from the Sushner line in males was 6.06/3.73 mm, in females 6.50/4.31 mm; the average value of the Merrifield angle in males was 71.51°, and in females 69.57°; Conclusion: By comparing the results, a statistically significant difference in genders was observed for a distance of the upper and lower lip from the Ricketts line, along with the distance of the upper lip from the Steiner line. The results of this study correspond to the results found in the literature. Keywords: lips; position of lips; reference lines; morphometry; aesthetics